The Ashgate research companion to political violence - Breen-Smyth, Marie (Ashgate research companion, 2016)
pt. 1. Defining political violence -- pt. 2. Motivations and goals of political violence -- pt. 3. Theorising, understanding and researching political violence -- pt. 4. Manifestations of political violence -- pt. 5. Countering political violence -- pt. 6. Ending political violence -- pt. 7. Dealing with the aftermath.